Perancangan Sistem Informasi Geografis Untuk Pemetaan Rumah Kos Berbasis Web Di Kota Batam - les lie mervin; Darmansah Darmansah (Computer Based Information System Journal, 2025)
The design of this system is done to develop a web-based Geographic Information System (GIS) to help map boarding houses in Batam City. The development of this system is done using the Extreme Programming (XP) method, which emphasizes short iterations, and collaboration between developers and users. This system is designed by providing information about boarding houses. such as, boarding house location, facilities, prices, boarding house photos, boarding house types, boarding house web addresses, and their availability. The main features developed are mapping of boarding house locations with leaflet and OpenStreetMap integration, filters for searching based on price, facilities and type, and the ability for boarding house owners to add, edit, or delete boarding house data. Testing of this system is done using the black-box testing method, which shows that the entire system functions according to plan without any failures and errors. The results of the study of this system increase the ease of access to information for prospective boarding house tenants and provide a platform for boarding house owners to market their properties, as well as attract prospective boarding house tenants. The implementation system is expected to be a solution to overcome the problem of marketing boarding houses in Batam City, as well as making it easier for prospective boarding house tenants to find boarding house locations that suit their needs.